Experimental performance and response surface modelling of solar dryer for drying of bitter gourd in Western Maharashtra, India - Yadav, Aditya Arvind; Prabhu, Pravin A; Bagi , Jaydeep S (Journal of Postharvest Technology, 2021)
The current study focuses on the performance of solar greenhouse dryer for drying of bitter gourd in solar greenhouse dryer and open sun condition in Western Maharashtra. The bitter gourd is also known as Momordica charantia is one of the important vegetable crops. The high water content in the crop yields to biological loss. Therefore, there is a need to preserve the bitter gourd by drying for a non-seasonal requirement. The experiment was conducted for drying of bitter gourd in solar greenhouse dryer and open sun condition on 6th of April 2021 from 7 am to 7 pm, for 12 hours respectively. The experimental observations collected during experimentation were set as input data for the Design of Experiments i.e., for Response Surface Modelling (RSM). The contour plot obtained during modeling resembles the optimum region of drying, the optimum region for drying of bitter gourd is 40 to 50o C respectively. The moisture removal rate (MRR) for drying of bitter gourd in solar greenhouse dryer and open sun drying is 90 and 88 %, respectively. The drying rate observed during the experiment has a better resemblance with simulated Response Surface Modelling.